Disease-associated variants of Gap Junction Beta 2 protein (GJB2) in the deaf population of Southern Punjab of Pakistan - Nabila Kausar (Public Library of Science (PLoS), 2021)
Hearing impairment (HI) is a highly heterogeneous genetic disorder and is classified into nonsyndromic (without any other clinical manifestations) and syndromic (if combined with other clinical presentations) forms. Variations in GJB2 gene are the leading cause of autosomal recessive nonsyndromic hearing loss (ARNSHL) in several populations worldwide. This study was carried out to investigate the prevalence of GJB2 variations in severe-to-profound hearing impaired families of Southern Punjab of Pakistan. Ten families segregating ARNSHL were recruited from different areas of the region. Sanger sequencing of GJB2 coding region was carried out. In two out of ten families, NM_004004:c.*71G>A (p.(Trp24*)) and NM_004004:c.358_360del (p.(Glu120del)) homozygous variants were identified as the cause of hearing loss. Our study showed that GJB2-related hearing loss accounts for at least 20% of all cases with severe-to-profound hearing loss in the Southern Punjab population of Pakistan.